Telaah Pergeseran Paradigma Penetapan Harga melalui Algorithmic Price Fixing - Rickra Christy Alexandra; Kukuh Tejomurti; Sasmini Sasmini (Indonesian Publication Center, 2026)
This study aims, first, to analyze the harmonization of regulatory frameworks between the OECD standard setting concerning algorithmic collusion and the provisions of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Second, this study seeks to formulate legal harmonization measures that can be undertaken to address collusive practices arising from the use of artificial intelligence–based pricing algorithms. This research constitutes normative legal research employing a conceptual approach. The findings indicate that there remains a regulatory disharmony between Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and the OECD standard setting related to algorithmic collusion. Legal harmonization measures may be carried out through the reform of legal instruments as well as the strengthening of the institutional role of the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha).